Analisis Kelayakan Ekonomi pada Rencana Penggantian Alat Mekanis Penambangan Batubara Di PT XYZ, Kabupaten Tanah Bumbu, Provinsi Kalimantan Selatan - Gading Abi Pangestu; Riswan Riswan; Karina Shella Putri (MINERAL, 2021)
PT XYZ plans to replace the production unit of the Kobelco SK200 excavator because it is unable to achieve the production target with a Mechanical Availability (MA) value of 55%. There are 7 scenarios in considering the replacement of the equipment. The analysis is carried out by considering the unit's capability and value in Net Present Value (NPV), Internal Rate of Return (IRR), and payback period in each scenario. The scenario for the improvement of Kobelco SK200 which increases the MA value to 75% is still unable to achieve the production target. Economic analysis shows that the highest NPV is in scenario 4 of Rp. 22,240,168,298, while the highest IRR is in scenario 3 of 79.93%. If PT XYZ wants a faster payback duration, scenario 3 by selling old equipment and renting used equipment with an MA value according to the target is the best choice. In addition, in terms of capital requirements, scenario 3 is the option with the lowest initial capital, where the amount of capital is a very important factor and often limits the ability of entrepreneurs and mining companies.